Anomalous Hall Effect in Epitaxial Thin Films of the Hexagonal Heusler MnPtGa Noncollinear Hard Magnet. Issue 36 (9th November 2022) - Ibarra, Rebeca; Lesne, Edouard; Sabir, Bushra; Gayles, Jacob; Felser, Claudia; Markou, Anastasios
Abstract: Materials hosting noncollinear magnetic ordering and sizeable spin‐orbit coupling can manifest perpendicular magnetic anisotropy and a Berry curvature‐driven intrinsic anomalous Hall effect. In this work, the structural, magnetic, and magnetotransport properties of crystalline hexagonal Heusler MnPtGa epitaxial thin films are reported. The centrosymmetric MnPtGa films ( P 63 / mmc space group) crystallize with a preferred c ‐axis (0001) crystal orientation. Along this crystallographic direction, the MnPtGa films exhibit preferential perpendicular magnetic anisotropy, below the Curie temperature T C = 263 K, with a large effective uniaxial magnetic anisotropy K eff  = 0.735 MJ m −3, at 150 K. In addition, the MnPtGa system undergoes a thermally induced spin reorientation transition below T sr = 160 K, which marks the onset of a noncollinear spin‐canted state. The anomalous Hall conductivity (AHC) of MnPtGa films exhibits a nonmonotonic behavior as a function of temperature, which changes sign at T*  = 110 K. Concurrently with the reported unusual dependence of the AHC on the longitudinal conductivity in MnPtGa crystalline thin films, these findings strongly suggest an anomalous Hall effect of intrinsic origin, driven by a momentum‐space Berry curvature mechanism, as supported by first‐principle calculations. Abstract : The unusual dependence of the anomalous Hall conductivity (AHC) on the longitudinal conductivity in epitaxial thin films of the hexagonal Heusler MnPtGa noncollinear hard magnet is reported, which further exhibit a peculiar case of concomitant zero AHC at finite temperature and nonzero spontaneous magnetization. These findings strongly suggest an anomalous Hall effect deriving from an intrinsic momentum‐space Berry curvature mechanism.